2005
DOI: 10.1152/ajplung.00177.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of thromboxane A2-mediated contraction in pulmonary veins

Abstract: [Ca 2ϩ ]i and myofilament Ca 2ϩ sensitivity in the pulmonary venous smooth muscle (PVSM) contractile response to the thromboxane A2 mimetic U-46619 and to assess the roles of PKC, tyrosine kinases (TK), and Rho-kinase (ROK) in that response. We tested the hypothesis that U-46619-induced contraction in PVSM is mediated by both increases in [Ca 2ϩ ]i and myofilament Ca 2ϩ sensitivity and that the PKC, TK, and ROK signaling pathways are involved. Isometric tension was measured in isolated endothelium-denuded (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 40 publications
2
25
2
Order By: Relevance
“…Activated PKC could activate Ca 2ϩ -channels that would contribute to increases in intracellular calcium concentration, participating in agonist-induced contraction (Fish et al, 1988;Navedo et al, 2005). PKC activity could also potentiate contraction by enhancing calcium sensitivity of contractile mechanisms (Gokina et al, 1999;Ding and Murray, 2005), an effect also demonstrated in human arteries (Martínez et al, 2000). In fact, PKC participates in calcium-sensitizing pathways of contraction of rabbit corpus cavernosum smooth muscle (Takahashi et al, 2003).…”
Section: Pkc and Tp Receptors In Diabetic Human Penis 785mentioning
confidence: 98%
“…Activated PKC could activate Ca 2ϩ -channels that would contribute to increases in intracellular calcium concentration, participating in agonist-induced contraction (Fish et al, 1988;Navedo et al, 2005). PKC activity could also potentiate contraction by enhancing calcium sensitivity of contractile mechanisms (Gokina et al, 1999;Ding and Murray, 2005), an effect also demonstrated in human arteries (Martínez et al, 2000). In fact, PKC participates in calcium-sensitizing pathways of contraction of rabbit corpus cavernosum smooth muscle (Takahashi et al, 2003).…”
Section: Pkc and Tp Receptors In Diabetic Human Penis 785mentioning
confidence: 98%
“…It is widely known that muscle contraction is not only the result of an increase in intracellular Ca 2ϩ concentration, but also Ca 2ϩ sensitization (32). U46619 induces smooth muscle contraction in certain tissues by Ca 2ϩ sensitization in a manner that is reversible by the Rho-kinase specific inhibitor Y27632 (33)(34)(35). To evaluate the Rho-kinase pathway involvement in the U46619-induced fetal bronchial peristatic activity we progressively increased the Y27632 concentration of pre-stimulated bronchial muscle until a significant reduction in tonic force was observed.…”
Section: Fetal Bronchial Muscle Rhythmic Activitymentioning
confidence: 99%
“…Other cells, including macrophages and monocytes, contribute to TXA 2 generation via both COX-1 and COX-2 with the latter isozyme being particularly relevant during infl ammation ( 2,5 ). TXA 2 acts as a local autocrine or paracrine mediator to mediate a range of physiological and pathophysiological responses that include platelet activation, vasoconstriction, and smooth muscle cell proliferation ( 3,(6)(7)(8)(9)(10). These processes are of particular relevance to cardiovascular disease (CVD) in which TXA 2 generation is markedly elevated and expression of its receptor, the TXA 2 receptor (TP), is increased (11)(12)(13).…”
mentioning
confidence: 99%